The Role of Micro, Small, and Medium Enterprises (MSMEs) in Central Kalimantan in Community Economic Welfare - Dedi Takari; Dicky P. Ompusunggu; Mutia Angelina Sari (Pelopor Publikasi Akademika, 2025)
This study aims to analyze the role of Micro, Small, and Medium Enterprises (MSMEs) in improving community economic welfare in Central Kalimantan. The method used in this study is the literature study method, which involves collecting and reviewing relevant literature based on available library data and then organizing it to support the analysis. The findings indicate that MSMEs play a significant role in fostering local economic development by creating jobs, stimulating economic growth, and reducing poverty. These enterprises also contribute to the empowerment of local communities by providing opportunities for entrepreneurship and skill development. Furthermore, MSMEs support the development of the broader economy by strengthening local supply chains and enhancing the overall economic resilience of the region. Based on the findings, the study provides recommendations for increasing the role of MSMEs in Central Kalimantan, such as improving access to finance, enhancing business infrastructure, offering training programs, and encouraging government policies that support MSME development. The study highlights the importance of fostering a conducive environment for MSMEs to thrive, ultimately contributing to the sustainable economic welfare of the community.